Polyvinylidene fluoride and polyetherimide hollow fiber membranes for carbon dioxide stripping in gas-liquid membrane contactor - Rosmawati, Naim (2014)
Porous polyvinylidene fluoride (PVDF) and polyetherimide (PET) hollow fiber membranes were developed for CO 2 stripping in membrane contactor system. The effects of various types of additives (lithium chloride, polyethylene glycol, phosphoric acid, methanol and glycerol) and different concentrations of lithium chloride (LiC1) on the membrane structure and CO 2 stripping performance of PVDF membrane were investigated. Different polymer concentrations of PEI membranes were studied and their effects on membrane structure and CO 2 stripping performance were evaluated. Long term performance of PVDF and PEI membranes were compared and analyzed. The membranes were characterized in terms of gas permeation, contact angle, membrane porosity, liquid entry pressure and tensile strength. Atomic force microscopy (AFM) was used to examine the membrane surface roughness while the membrane morphology was investigated using scanning electron microscopy (SEM) and field emission scanning electron microscopy (FESEM). Mass transfer resistance of the system was further calculated based on the experimental data. The addition of additives improved the PVDF membrane characteristics in terms of liquid entry pressure and stripping flux. This could be caused by the thermodynamic (polymer-solvent interaction) and kinetic effects (solution viscosity) on the phase inversion process. These effects also contributed to the reduction of membrane pore size, contact angle and gas permeability of PVDF membranes. The CO 2 stripping performance of PVDF with polyethylene glycol (PEG) additive showed the highest stripping flux and efficiency compared to the other membrane samples. The increase in the concentration of LiC1 in PVDF membrane produced high stripping fluxes which can be associated to low surface roughness and mass transfer resistance. For PET membrane, increasing the polymer concentration had significantly enhanced the wetting pressure whilst reducing the gas permeation. From FESEM analysis, PEI hollow fiber membranes showed finger-like structure similar to PVDF membrane but there was variation in thickness of spongelike layer in the middle of the membrane cross-structure. Comparative study between PVDF and PEI hollow fiber membranes possessed different microstructures with PVDF-PEG membrane achieving the highest stripping flux of 4.Ox 10-2 mol/m2s. Although PEI membranes had higher resistance compared to PVDF membranes in terms of liquid entry pressure, both membranes suffered reduction of stripping flux after operating more than 20 hours. However, the percentage of flux reduction during long hour operation for PVDF membrane was 34% higher than PEI membrane. In addition, PVDF membranes demonstrated higher stripping flux compared to PEI membranes. Therefore, highly hydrophobic membranes with reasonable pore sizes and microstructure are preferred in membrane contactor system for CO 2 stripping application.